EXPERIENCE OF THE INPUT-OUTPUT MODELS APPLICATION TO THE MOLDOVAN ECONOMY - NAVAL, Elvira (Economy and Sociology, 2021)
The main goal of this article is to present an overview of the input-output models which have been applied to Moldovan economy development study. We examined: static input-output model, dynamic input output model restricted by limited energy resources, and the Markov chain approach based on the input output tables. All these models have been examined using statistic data referring to the input-output table, constructed on the base of 19 and 16 aggregated branches of the national economy. Static and dynamic optimization models were formulated, simulation calculation was done and analysed. Input-output table balancing problem was solved using RAS method. For dynamic model matrix of the investment coefficients was constructed. The emphasis was put on the problem of applying the theory of Markov chain for examination of the 19 and 16 branches in the framework of the input-output model for Republic of Moldova. A square exchange matrix of order n x n has been constructed. Every branch was considered as one state of the Markov chain with n states. We introduced a new (n + 1) -th absorption state so that the examined matrix became of the order ( n + 1) x ( n + 1) . The obtained transition matrix – probabilities matrix has been used for forecasting.